Quo vadis transformasi digital: tantangan optimalisasi peradilan elektronik (e-court) dalam penyelesaian sengketa tata usaha negara - fiska bella (Jurnal Hukum Lex Generalis, 2024)
Digital transformation within the Supreme Court is also being implemented at the State Administrative Court (PTUN) with the use of electronic justice or e-court. This modernization aims to transform the scourge of justice in Indonesia, which is complicated, time-consuming and expensive, into simple, fast and cheap justice. This shift in conception from conventional to digital raises various challenges that must be answered, the need for strengthening regulations, the readiness of legal instruments and also adequate infrastructure to be able to keep up with the dynamic escalation of digital transformation. Strategic steps are needed to be able to implement e-courts optimally in Indonesia.